CELL NON-AUTONOMOUS MECHANISMS OF AGING. (8th November 2019) - Leiser, Scott
Abstract: It is now recognized that biological aging can be affected both positively and negatively by intercellular communication. This symposium will focus on recent discoveries related to cell non-autonomous mechanisms of aging.